CSB interacts with BRCA1 in late S/G2 to promote MRN- and CtIP-mediated DNA end resection - Batenburg, Nicole L (Nucleic Acids Res, 2019)
CSB, a member of the SWI2/SNF2 superfamily, has been implicated in evicting histones to promote the DSB pathway choice towards homologous recombination (HR) repair. However, how CSB promotes HR repair remains poorly characterized. Here we demonstrate that CSB interacts with both MRE11/RAD50/NBS1 (MRN) and BRCA1 in a cell cycle regulated manner, with the former requiring its WHD and occurring predominantly in early S phase. CSB interacts with the BRCT domain of BRCA1 and this interaction is regulated by CDK-dependent phosphorylation of CSB on S1276. The CSB–BRCA1 interaction, which peaks in late S/G2 phase, is responsible for mediating the interaction of CSB with the BRCA1-C complex consisting of BRCA1, MRN and CtIP. While dispensable for histone eviction at DSBs, CSB phosphorylation on S1276 is necessary to promote efficient MRN- and CtIP-mediated DNA end resection, thereby restricting NHEJ and enforcing the DSB repair pathway choice to HR. CSB phosphorylation on S1276 is also necessary to support cell survival in response to DNA damage-inducing agents. These results altogether suggest that CSB interacts with BRCA1 to promote DNA end resection for HR repair and that although prerequisite, CSB-mediated histone eviction alone is insufficient to promote the pathway choice towards HR.